Proyecto de factibilidad para la implementación de una vulcanizadora automática para vehículos livianos en el cantón Catamayo - Castillo Ortega, Carlos Alberto (2016)
This feasibility study will reveal the feasibility of implementing an automatic vulcanizer for light vehicles in the canton Catamayo, for which, methodologies for conducting the market study were inductive, deductive, descriptive, analytical method was applied and survey techniques and direct observation. This service is aimed at owners of light vehicles, residents, who wish to acquire the services of vulcanized tires, plus service and tire balancing enllantaje quickly, safely, using specific equipment for each service. That is why a project feasibility to implement an automatic vulcanize for light vehicles in the canton Catamayo, which is the market segment that will be targeted surveys based on the size of the sample had 388 surveys were developed apply, the same that will be of vital importance to the comfort and safety of people seeking these services, optimizing time, at affordable prices while maintaining quality and good service. Through market research was obtained that there unmet demand of 196,128 vulcanized tire services in the city of which must be harnessed through project implementation. Through technical study it determined that the installed capacity of self-vulcanizing be 20.952 annual services and will start with 60% capacity utilization split the first year, taking the requirements of each of the resources, materials and equipment necessary for the operation of the company. The organizational structure provides for the establishment of a limited liability company whose corporate name is: Vulcanizadora AUTOMATIC "CATAMAYO TIRES. CIA. LTDA. ", And its functional organization can establish that the company will have both administrative and operational human resources trained according to their functions, with defined and specific responsibilities. With regard to the financial study found that a total investment of $ 31.966,24 will be required; also in the financial evaluation, the result of NPV resulted 17.587,07, the result was 30,32% IRR, Benefit Cost Ratio is at 1.36 Recovery Capital will be in 2 años and 9 monts and by Finally with the sensitivity analysis it was determined that the project is not sensitive to an increase in costs by up to 15,46% and a decrease in revenue of up to 11,45%. When performing financial analysis, it was learned that the project is viable, ts implementation is feasible because you can recover the initial investment in the medium term. By the results it has been determined that there is unmet demand for vulcanizing services in the city of Catamayo and it was concluded that this project is feasible to do one hundred percent.